APPLICATION OF INVENTORY TURNOVER ANALYSIS ON INDONESIAN MINISTRY/AGENCY FINANCIAL STATEMENT - Rianto, Laskar (Badan Pemeriksa Keuangan Republik Indonesia, 2019)
Inventory turnover is a simple accounting analysis method seldom used by the user of Indonesian governmental organization?s financial statement due to lack of accrual information in the past. The opportunity for the application of this analysis arrived in 2015 along with the implementation of accrual accounting basis by the Indonesian government. This study observes the Indonesian ministry/agency (MA) inventory management focusing on the inventory average flow time, during the 2017 and 2018 period. The study shows that among 86 MAs, 62 MAs have desired average flow time. The other 24 MAs have high average flow time with 12 of them also have unstable average flow time. While several MAs disclosed information related to their average flow time, most MAs did not. Thus, they failed to communicate their conditions to their stakeholders. The average flow time can be used as a starting point for the managers, auditors, and other stakeholders to further analyze government inventory management. Better inventory management can reduce costs and improve the government planning process. Therefore, the government may be capable of allocating their budget for other programs or activities to deliver higher value for the public.